New species and new records of Laboulbeniales (Ascomycota) from Sierra Leone - Rossi, Walter; Leonardi, Marco (Phytotaxa, 2018)
Nine new species of Laboulbeniales are described. These are Camptomyces africanus, parasitic on Astenus sp. (Coleoptera, Staphylinidae); Corethromyces golaensis, parasitic on Afrobium sp. (Staphylinidae); Diaphoromyces minutissimus, parasitic on Clavilispinus sp. (Staphylinidae); Laboulbenia antemnalis, parasitic on Macrotermes bellicosus (Isoptera, Termitidae); Laboulbenia buccalis, parasitic on Amitermes evuncifer (Termitidae); Laboulbenia insolita and L. kingsleyae, both parasitic on Abacetus pubescens (Coleoptera, Carabidae); Laboulbenia penetrans, parasitic on Stereocerellus singularis (Diptera, Chloropidae); Rhachomyces carbonii, parasitic on Tracypum sp. (Staphylinidae). Fourty-one species are reported for the first time from Sierra Leone, 12 of which are new for the whole African continent and 15 are recorded for the first time after description. A new synonymy is established: Kainomyces hyalinus Terada 1978 = K. alutellae Thaxt. 1931.